Pengembangan Sistem Informasi Pelelangan Kendaraan untuk Meningkatkan Efisiensi dan Transparansi Proses Lelang - Nilawati (Jurnal Sistem Komputer (SISKOM), 2022)
This study focuses on the development and implementation of a Vehicle Auction Information System to enhance the efficiency and transparency of the auction process. The system aims to streamline the management of vehicle auctions, from listing and bidding to final sale and documentation. Key features include real-time auction tracking, automated bidding, detailed vehicle listings with images and specifications, and secure payment processing. By integrating advanced data management and real-time communication technologies, the system ensures a smooth and transparent auction experience for both sellers and buyers. The research outlines the design, development, and deployment phases of the system, including the selection of appropriate technologies, system architecture, and user interface design. The implementation of this system is expected to lead to significant improvements in auction efficiency, participant engagement, and overall satisfaction. The paper also discusses the challenges encountered during the development and deployment phases, as well as the strategies adopted to overcome these challenges. Results indicate that the Vehicle Auction Information System effectively addresses the limitations of traditional auction practices and provides a scalable and reliable solution for organizations aiming to enhance their auction